Acute spinal cord infarction after multilevel en bloc corpectomy: a case report and literature review. Issue 11 (November 2021) - He, Shaohui; Zhang, Yue; Bi, Yifeng; Wei, Haifeng
Spinal cord infarction (SCI) is a catastrophic neurologic deficit following spine surgery. Because of the opposite management regimens used for SCI and acute epidural hematoma, accurate diagnosis of SCI is of great importance to maximally reserve neurologic functions and improve outcomes. A 21-year-old man developed acute paralysis and sensory deficits of the bilateral lower limbs shortly after undergoing two-stage combined posterior and anterior multilevel en bloc corpectomy. An emergency second-look surgery revealed wide-spectrum blackness of the thecal sac with no signs of an epidural hematoma. The patient underwent anticoagulation therapy, ventilation support, microcirculation perfusion, and fluid optimization. He regained an ambulatory status without other severe complications. Upon discharge, his muscle strength had returned to grade 4 and his Eastern Cooperative Oncology Group performance score had decreased to 0. At the final 48-month follow-up, the implants were in good position without local recurrence, and the patient was able to lead an independent life and work in his full capacity. An epidural hematoma did not appear to be the cause of SCI after spinal tumor surgery in this case; however, SCI was a possible reason for the acute paralysis. Anticoagulation treatment with adjuvant therapies may be an effective option in managing SCI.